Advances in Guidance, Navigation and Control Proceedings of 2024 International Conference on Guidance, Navigation and Control (Volume 15) - Yan, Liang; Duan, Haibin; Deng, Yimin (Lecture Notes in Electrical Engineering, 2025)
XIV, 604 p. 343 illus., 282 illus. in color.